Assessment of oxidative stress status and neuroprotection by vitamin E in chronic cerebral hypoperfusion-induced neurodegeneration in rats - Sayeed, Sayyada (Kulliyyah of Medicine, International Islamic University Malaysia, 2015)
Disorders of the cerebral circulation have been associated with various neurological illnesses in elderly. Alzheimer's disease (AD), the most eminent form of dementia, is an irremediable, escalating disorder characterized by gradual cell death in the hippocampus and the frontal cortex which in the long run leads to loss of intellectual abilities. A persistent reduction in regional cerebral blood flow (CBF) compromises memory and cognitive functions. To explicate the neuropathological consequences of a reduced CBF, a cognate condition has been created in rats by common carotid artery occlusion (2 vessel occlusion, 2VO). Oxidative stress, caused due to a disproportionate release of free radicals, has been associated with neuronal cell death in various regions of the brain. Enhanced production of reactive oxygen species (ROS) and perturbed antioxidant defenses determine the chemical changes in all cellular components resulting in their damage. The most promising strategy to mollify the effect of ROS-induced oxidative damage is through antioxidants. Vitamin E (Vit E), an effective lipid soluble antioxidant is speculated to break the propagation of the free radical chain reaction in the lipid part of the biological membrane and decrease lipid peroxidation which contributes to its antioxidant activity. After acclimatization, twenty four Sprague Dawley rats weighing 200-250 g were equally divided into three groups. Group A – sham control, Group B – 2VO, and Group C – 2VO+E (treated daily with Vit E, 100 mg/kg, orally following 2VO). On the 8th week, all the rats were euthanized and the hippocampi were isolated. Viable neuronal cell count in the hippocampal region was estimated. The Isoprostane F2 (F2-IsoPs) levels were deliberated in the brain homogenates to quantify the oxidative stress status. There was significant difference in neuronal cell death in 2VO group in comparison to the sham group. In 2VO+E rats, the viable neuronal cell count of the hippocampal region was significantly higher (p<0.05) as compared to the 2VO group. Moreover, F2-IsoPs levels in 2VO group was significantly higher (p<0.05) as compared to 2VO+E group, implying high oxidative stress in 2VO group and reduction of oxidative stress levels in 2VO+E group. This study demonstrated the effectiveness of Vit E as a neuroprotective and antioxidant agent in chronic cerebral hypoperfusion-induced neurodegeneration in rats.